Implementation of a Medical Coding Mentorship Program to Reduce BPJS Health Insurance Pending Claims at Sandi Karsa Hospital, Makassar - Agustina; Lilik Meilany; Asriyanti; Rosana Dwiyanti Putri (Abdimas Polsaka, 2026)
Background: In Indonesia’s National Health Insurance (JKN) system, the accuracy of medical coding plays a critical role in determining claim approval and reimbursement through the Indonesia Case Base Groups (INA-CBGs) payment mechanism. Inaccurate coding of diagnoses and procedures often results in pending BPJS Health claims, leading to delayed payments and increased administrative burden for hospitals. This community service activity aimed to implement and evaluate a mentoring program designed to improve medical coding practices and reduce pending BPJS Health claims at Sandi Karsa Hospital, Makassar. Methods: The program was conducted from August to October 2025 using a participatory and problem-solving approach. The activities included initial assessment of pending claims, theoretical training on ICD-10 and ICD-9-CM coding principles, case-based simulations using actual medical records, direct on-site mentoring during coding processes, and the development of a Standard Operating Procedure (SOP) for medical coding. Program evaluation was performed by comparing the number of pending claims related to coding errors before and after the intervention and by observing improvements in coding practices. Results: Prior to the intervention, 85 cases of pending claims were identified as being caused by coding rule errors. After the mentoring program was implemented, the number decreased to 34 cases, representing a reduction of approximately 60%. In addition, qualitative improvements were observed in the consistency of determining principal and secondary diagnoses, the accuracy of ICD-10 and ICD-9-CM code selection, and the overall quality of claim documentation. Conclusion: The mentoring-based intervention effectively improved medical coding accuracy and reduced BPJS pending claims at the hospital. Continuous training, regular coding audits, and the implementation of standardized coding procedures are recommended to sustain these improvements and support more efficient hospital claim management